Synthesis, Characterization, Antimicrobial of Studies New 2,2'-{(1Z,2Z)-ethane-1,2-Diylidenebis[(2Z) Hydrazin-1-yl-2-ylidene-1,3,4-oxadiazole-5,2-diyl]}Diphenol and their Transition Metal Complexes - Azhar Hameed Gatea (Journal of Global Pharma Technology, 2018)
A new ligand 2,2'-{(1Z,2Z)-ethane-1,2-diylidenebis[(2Z)hydrazin-1-yl-2-ylidene-1,3,4-oxadiazole-5,2-diyl]}diphenol and its Cr(III) , Co(lll) and Ni(ll) complexes were synthesized . The ligand and its complexes were characterized by elemental analysis, conductance measurements, as well as spectroscopy (H1NMR, IR, mass), magnetic susceptibility. A new ligand and its complexes were screened for their antibacterial activity against two kinds of strains Escherichia coli (gram negative bacterial strains) and staphylococcus aureus (gram positive bacteria strains) using the agar disk diffusion method.